Innovations in legal project management. (2021) - Leventon, Aileen; Bielawski, Kevin; Wasson, Lann; Davenport, Sam; Fanning, Brian; Wise Mendes, Meredith; Brater, Randall; Heilman, Katie; Kalogerou, Byron S; White, Dennis J; Hutchison, Todd; Agostinelli, Thomas; et al.
No abstract available